Applications of Molecular Modeling in Endocrinology- Review Article - Azadeh EBRAHIM-HABIBI; Bagher LARIJANI (Tehran University of Medical Sciences, 2015)
Modeling and simulation techniques are now widely used alongside with their experimental counterparts in order to complement them, or sometimes to bring first insights into the possible outcome of experiments. "Modeling" is a general word that could encompass a wide range of methods that could be applied to a variety of subjects and problems. Here, the use of selected molecular modeling methods has been described in the field of endocrinology, throughout of some concrete examples.   Keywords: Molecular modeling, Homology model, Docking, Endocrinology